2017
DOI: 10.1155/2017/7525179
|View full text |Cite
|
Sign up to set email alerts
|

Network Pharmacology‐Based Approach to Investigate the Analgesic Efficacy and Molecular Targets of Xuangui Dropping Pill for Treating Primary Dysmenorrhea

Abstract: This study aimed to evaluate the clinical analgesic efficacy and identify the molecular targets of XGDP for treating primary dysmenorrhea (PD) by a network pharmacology approach. Analysis of pain disappearance rate of XGDP in PD treatment was conducted based on data from phase II and III randomized, double-blind, double-simulation, and positive parallel controlled clinical trials. The bioactive compounds were obtained by the absorption, distribution, metabolism, and excretion processes with oral bioavailabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP) is an integrated systems pharmacology platform of Chinese herbal medicines that covers chemicals, targets and drug targets, as well as pharmacokinetic properties for compounds involving oral bioavailability, drug-likeness, blood-brain-barrier, intestinal epithelial permeability, aqueous solubility and etc [15]. In this study, oral bioavailability (OB) and drug-likeness (DL) were utilized to screen out the chemical constituents meeting OB ≥ 30% and DL ≥ 0.18 simultaneously [16]. In addition, the active ingredients with low oral bioavailability and remarkable e cacy reported in the literature were included.…”
Section: Identi Cation and Screen Of Candidate Compoundsmentioning
confidence: 99%
“…Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP) is an integrated systems pharmacology platform of Chinese herbal medicines that covers chemicals, targets and drug targets, as well as pharmacokinetic properties for compounds involving oral bioavailability, drug-likeness, blood-brain-barrier, intestinal epithelial permeability, aqueous solubility and etc [15]. In this study, oral bioavailability (OB) and drug-likeness (DL) were utilized to screen out the chemical constituents meeting OB ≥ 30% and DL ≥ 0.18 simultaneously [16]. In addition, the active ingredients with low oral bioavailability and remarkable e cacy reported in the literature were included.…”
Section: Identi Cation and Screen Of Candidate Compoundsmentioning
confidence: 99%
“…To investigate the underlying relationship between the targets interacting with the active ingredients in SMT, we built a PPI network comprised of 123 nodes and 333 edges for the myelosuppression-associated SMT targets ( Figure 4). e centralization and heterogeneity of the PPI network were 0.411 and 2.249, respectively, which suggested that the network may contain hubs, nodes with a large number of interactions [63,100,[103][104][105]. Here, a node was determined to be a hub if its degree is greater than or equal to twice the average node degree of the network [106,107].…”
Section: Network-based Analysis Of the Pharmacological Mechanisms Of mentioning
confidence: 99%
“…OB refers to the relative amount of drug absorbed into systemic blood circulation after administration by the extravascular route and reflects whether the compound has a key indicator of intrinsic activity. Many compounds fail to produce therapeutic effects due to the lack of kinetic characteristics (especially oral bioavailability) and are unable to reach in vivo targets [15]. The OB values were obtained on a bioinformatics system using the OBioavail 1.1 model, which calculates the relationship between the composition and the P4503A4 enzyme and transporter (p-glycoprotein).…”
Section: Adme Screening Of the Ygl Capsulementioning
confidence: 99%